Immunization with outer membrane vesicles drived Proteus mirabilis protects mice against bacteria-induced lethality - Fan, Wei; Zhai, Yilu; Zhang, Xinyu; Sun, Fuliang; Kong, Lin; Wang, Wei; Zhao, Dazhuo; Fu, Jiaqi (Frontiers in Immunology, 2025)
IntroductionProteus mirabilis (Pm) has emerged as a significant and widespread opportunistic pathogen affecting both humans and animals, resulting in substantial economic losses within the agricultural sector. While most conventional antibiotics remain effective against Pm infections, the rise of multidrug-resistant strains has considerably complicated disease management. Outer membrane vesicles (OMVs), which are vesicular structures secreted by Gram-negative bacteria, have been identified in numerous studies as potential antigenic components or immune adjuvants for the development of novel vaccines.MethodsIn this study, Proteus mirabilis outer membrane vesicles (Pm_OMVs) were employed to immunize mice, followed by the execution of Pm infection assays. The immune responses elicited by Pm_OMVs and their protective effects in the Pm infection mice were evaluated using quantitative PCR, ELISA, and Western blot analyses.ResultsOur findings demonstrated that Pm_OMVs stimulated B cells to produce specific antibodies and induced Th1/Th17-mediated immune responses. Following 24 hours of Pm infection, Th1 and Th17 cells in the Pm_OMVs-infected group were activated, releasing substantial levels of cytokines that facilitated rapid bactericidal activity. After 72hours of Pm infection, Th2 and Treg cells in this group were activated to suppress excessive inflammatory response and achieve tissue repair. Pm_OMVs also specificall increased the survival rate of mice infected with Pm, up to 80%.DiscussionThese results suggest that Pm_OMVs can be used as an effective material to prevent Pm infection.